Pyrrolyl and Indolyl α-γ-Diketo Acid Derivatives Acting as Selective Inhibitors of Human Carbonic Anhydrases IX and XII - Davide Ialongo; Antonella Messore; Valentina Noemi Madia; Valeria Tudino; Alessio Nocentini; Paola Gratteri; Simone Giovannuzzi; Claudiu T. Supuran; Alice Nicolai; Susanna Scarpa; Samanta Taurone; Michele Camarda; et al. (MDPI AG, 2023)
Solid tumors are active tissues containing hypoxic regions and producing metabolic acids. By decreasing pH, cancer cells create a hostile environment for surrounding host cells and foster tumor growth and progression. By governing acid/base regulation, carbonic anhydrases (CAs) are involved in several physiological/pathological processes, including tumors. Indeed, CAs are clinically relevant in cancer therapy as among the fifteen human isoforms, two of them, namely CA IX (overexpressed in solid tumors and associated with increased metastasis and poor prognosis) and CA XII (overexpressed in some tumors) are involved in tumorigenesis. Targeting these two isoforms is considered as a pertinent approach to develop new cancer therapeutics. Several CA inhibitors (CAIs) have been described, even though they are unselective inhibitors of different isoforms. Thus, efforts are needed to find new selective CAIs. In this work, we described new diketo acid derivatives as CAIs, with the best acting compounds 1c and 5 as nanomolar inhibitors of CA IX and XII, being also two orders of magnitude selective over CAs I and II. Molecular modeling studies showed the different binding poses of the best acting CAIs within CA II and IX, highlighting the key structural features that could confer the ability to establish specific interactions within the enzymes. In different tumor cell lines overexpressing CA IX and XII, the tested compounds showed antiproliferative activity already at 24 h treatment, with no effects on somatic not transformed cells.